Comparative analysis of traditional and UAV bridge inspections performed by New Mexico State University - Navarro-Montero, Valeria (Instituto Tecnológico de Costa Rica, 2023)
This research paper presents a comparative analysis between UAV-assisted inspection and traditional bridge inspection methodologies, focused on evaluating their performance. Aiming to identify the differences in inspection results and assess the efficiency of UAV-assisted inspections. Three specific objectives were defined to achieve the research goal. Firstly, the inspection results at the elemental level were compared between the two methodologies. The elemental condition summaries from each inspection were analyzed, and statistical analysis revealed a maximum variation of 16.1% and an error of 20.5% compared to traditional values. Secondly, the performance of each inspection methodology was calculated using the Lean philosophy. On-site measurements during the inspection were collected and classified according to the Lean principles. Founding that UAV-assisted inspections required approximately twice as much time as traditional inspections. Lastly, the relationship between inspection results and performance was examined. The UAV-assisted inspection allowed for the inspection of previously inaccessible elements such as piles, resulting in increased inspection time. This research contributes to understanding the performance and results of UAV-assisted inspections compared to traditional methods. The study emphasizes the importance of statistical analysis, Lean productivity measurements, and the consideration of inaccessible areas in bridge inspections.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2023.
Keywords: Condición de elemento; Lean; Análisis comparativo; Inspección -- Puentes; Evaluación de rendimiento; Mediciones -- Productividad; Inspección -- UAV; Element condition; Comparative analysis; Performance evaluation; Measurements -- Productivity; Inspection -- UAV; Inspection -- Bridges; Research Subject Categories::TECHNOLOGY::Engineering mechanics::Construction engineering